Pengaruh Viral Marketing, Celebrity Endorser, dan Brand Awerness terhadap Keputusan Pembelian Pada Geprek Bensu Karawang - Novita Karisma; Rafa Naufal Hanifah (Universitas Batanghari, 2023)
The increasingly advanced era makes the needs of each individual increase. In addition, the development of the times also greatly impacts the technology that changes very quickly from time to time. Now technology is born to make it easier for people to carry out their daily lives where we know that today's society wants everything to be instant. From this, companies must be able to understand how consumers make decisions to buy a product. This study aims to determine whether there is a significant influence of viral marketing, celebrity endorsers, and brand awareness on purchasing decisions at Geprek Bensu Karawang. The sampling technique uses Non Probability Sampling, namely the Incidental Sampling technique with a total of 30 respondents. The results of the study show that Viral Marketing, Celebrity Endorser, and Brand Awareness simultaneously have a positive and significant effect on purchasing decisions at Geprek Bensu Karawang, Viral Marketing partially has no significant effect on purchasing decisions at Geprek Bensu Karawang, Celebrity Endorser partially has a positive and significant effect on purchasing decisions at Geprek Bensu Karawang, Brand Awareness partially has a positive and significant effect on purchasing decisions on Geprek Bensu Karawang.